A hybrid robust-stochastic approach to evaluate the profit of a multi-energy retailer in tri-layer energy markets. (1st January 2021) - Zare Oskouei, Morteza; Mirzaei, Mohammad Amin; Mohammadi-Ivatloo, Behnam; Shafiee, Mahmood; Marzband, Mousa; Anvari-Moghaddam, Amjad
Abstract: Nowadays, multi-energy consumers in the industrial sector have a significant contribution in exchange of different forms of energy such as electricity, heat, and natural gas. So, multi-energy consumers can provide excellent opportunities for market players to trade power in various energy markets. In this paper, a new entity called multi-energy retailer is introduced to simultaneously meet both flexible and non-flexible electrical, gas, and heat demands of multi-energy consumers, with a high level of supply reliability. The multi-energy retailer is equipped with cogeneration facilities and various storage technologies such as power-to-x storages to exploit the actual arbitrage opportunities in different layers of energy markets. The presented structure successfully models the behavior of multi-energy retailer entity and seeks to maximize its profit as well as increase the welfare level of the multi-energy consumers. The uncertainties associated with electricity market price and various demands of multi-energy consumers can affect the profit and optimal day-ahead scheduling of the multi-energy retailer. In order to accurately model such uncertainties, a hybrid robust-stochastic approach is utilized in this study. This approach helps the multi-energy retailer's operator to evaluate the worst-case of the scheduling process for the entity. Finally, the profit of the multi-energy retailer entity is estimated in the presence of conversion facilities, demand response programs, and various uncertainties based on actual energy market data. Highlights: A new entity is introduced to meet energy demands of multi-energy consumers. The role of P2X units is examined in exploiting opportunities in energy markets. The impact of DRPs is investigated on the MER′ profit.